2020
DOI: 10.21203/rs.2.11510/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tele-transitions of Care (TTOC). A 12-month, Randomized Controlled Trial evaluating the use of Telehealth to achieve Triple Aim Objectives.

Abstract: Background: Poor transitions of care leads to increased health costs, over-utilization of emergency room departments, increased re-hospitalizations and causes poor patient experiences and outcomes. This study evaluated Telehealth feasibility in improving transitions of care.Methods: This is a 12-month randomized controlled trial, evaluating the use of telehealth (remote patient monitoring and video visits) versus standard transitions of care with the primary outcomes of hospital readmission and emergency depar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Taken in combination with minimal privacy concerns, these findings are consistent with past research. [22][23][24][25] To continue upholding this quality of care without incurring any privacy concerns, providers and their clients alike must be permitted flexibility in the type of telehealth platform they use. Given that unencrypted, nonpublicly facing telecommunications platforms (e.g., FaceTime) allowed for easier connections and resulted in no accidental breaches of private medical data, federal legislators could amend HIPAA to codify such leniency for telehealth into the law.…”
Section: Discussionmentioning
confidence: 99%
“…Taken in combination with minimal privacy concerns, these findings are consistent with past research. [22][23][24][25] To continue upholding this quality of care without incurring any privacy concerns, providers and their clients alike must be permitted flexibility in the type of telehealth platform they use. Given that unencrypted, nonpublicly facing telecommunications platforms (e.g., FaceTime) allowed for easier connections and resulted in no accidental breaches of private medical data, federal legislators could amend HIPAA to codify such leniency for telehealth into the law.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study conducted in the USA in 2020, it was found that medication compliance was 7 times higher in patients discharged from the hospital and followed up with a telehealth system for 12 months. No significant difference was observed between the rates of consulting emergency departments and hospitalization of the patients (15).…”
Section: Remote Patient Monitoring (Monitorization)mentioning
confidence: 76%
“…Schmaderer et al (2016) determined lower patient activation scores were associated with higher levels of acute care utilization, while Coleman et al (2004) and Chen et al (2018) determined person-centered transition planning across settings resulted in lower levels of acute utilization in the time period following discharge. Like Noel et al (2020), Bull et al (2000) did not find a statistically significant ○ Self-report Noel et al (2020) difference in patient participation efforts and post-discharge utilization, but did identify lower readmissions. Kvale et al (2016) examined utilization through a primary care follow-up lens and determined higher patient activation levels did not increase the likelihood of attendance, though did identify statistically significant lower perceptions of care involvement for myocardial infarction patients that completed cardiac rehabilitation post-discharge.…”
Section: Healthcare Utilizationmentioning
confidence: 80%
“…Patient and healthcare team partnerships in individualized transition planning led to higher perceived health, satisfaction with planning, and a greater feeling of preparedness. Ulin et al (2016) determined early discharge planning and communication between the hospital and community healthcare team members resulted in shorter hospital stays, while Noel et al (2020) found statistically significant greater medication adherence and positive feedback for those participatory in a telehealth care-transitions program. In the study by Arnetz et al (2010), an inverse relationship between patient ratings of planning inclusion and goal achievement was identified.…”
Section: Quality Outcomesmentioning
confidence: 99%